Glitter bomb - Childs, Laura; Moran, Terrie Farley (Childs, Laura. Scrapbooking mysteries., 2018)
It's Mardi Gras in New Orleans and scrapbook shop owner Carmela Bertrand is excited to be attending the Pluvius Parade along with her best friend Ava. Carmela's ex-husband Shamus rides by the duo on his float at the head of the parade, when suddenly the revelry turns to disaster. Shamus' float crashes and explodes, and although Shamus escapes unhurt, a member of his krewe is killed. Carmela and Ava plunge into an investigation of the krewe-member's death, but as they dig deeper it starts to look less like an accident and more like a murder....and Shamus seems less like a victim, and more like a suspect.